KERAGAAN TIGA VARIETAS PADI ADAPTIF LAHAN RAWA LEBAK YANG DITANAM PADA UMUR BIBIT BERBEDA - Hatna Hatna; M. Rizki Norfajerin; Lindawati Lindawati; Nurul Istiqomah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Planting adaptive varieties is one of the important efforts that need to be taken so that productivity is higher, resistant to pests and diseases. Seeds are an important component of production technology to obtain optimal production levels. This study aims to determine (i) the best interaction, (ii) the best adaptive varieties (iii) the best seedling age. This research was conducted in Muara Tapus Village from March to September 2021. Using a factorial Randomized Block Design (RBD). The first treatment was varieties with 3 levels, namely Ciherang, Cisokan Putih, and Mekongga, the second treatment was seedling age with 5 levels, namely seedling age of 30, 25, 20, 15, and 10 days. The results showed that the best interaction resulted from the Cisokan Putih variety treatment with 30 days of seedling age. Cisokan Putih variety and seedling age of 30 days are the best adaptive varieties and seedling age.